2021
DOI: 10.23960/jhptt.22182-90
|View full text |Cite
|
Sign up to set email alerts
|

Cross Application of Entomopathogenic Fungi Raw Secondary Metabolites for Controlling Fusarium Wilt of Chili Seedlings

Abstract: Cross application of entomopathogenic fungi raw secondary metabolites for controlling fusarium wilt of chili seedlings. Theresearch aimed to determine the effect of entomopathogenic fungi raw secondary metabolites on fusarium wilt on chili plants and on growth of chili. In vitro test used a Completely Randomized Design with 5 treatments and 5 replicate and in planta using a Randomized Block Design with 5 treatments and 5 replicatie including control, secondary metabolites of Beauveria bassiana B10, B. bassiana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…yang menginfeksi jaringan xylem terus berkembang sehingga jaringan menjadi rusak dan berubah warna menjadi coklat. Menurut Semangun (2004), jika tanaman memperlihatkan gejala serangan patogen lebih lama, maka pembentukan diskolorasi xylem dan perubahan warna yang terjadi lebih pendek.…”
Section: Panjang Diskolorasi Xylemunclassified
“…yang menginfeksi jaringan xylem terus berkembang sehingga jaringan menjadi rusak dan berubah warna menjadi coklat. Menurut Semangun (2004), jika tanaman memperlihatkan gejala serangan patogen lebih lama, maka pembentukan diskolorasi xylem dan perubahan warna yang terjadi lebih pendek.…”
Section: Panjang Diskolorasi Xylemunclassified
“…The production of spores and metabolites, such as antibiotics, enzymes, and pigments from filamentous fungi, has taken on global importance for the biological control of pests and biotechnological purposes [1][2][3][4][5]. These metabolites have been produced using fermentation systems, such as submerged fermentation (SmF) and solid-state fermentation (SSF), which differ in the nature of their operating conditions [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This molecule has attracted attention for its antimicrobial activities against bacterial and fungal phytopathogens [13,16,17], but it also exhibits cytotoxic properties [12,13,18]. Conversely, it has been observed that the use of fermented crude extracts (raw secondary metabolites) of B. bassiana benefits plant growth, inhibits the development of diseases caused by plant pathogenic fungi, and contributes to the production of phenolic compounds [5]. Instead of the use of synthetic insecticides and fungicides, biological control using spores and even metabolites represent a safe and feasible alternative for the control of pests [19], but production systems should be developed to obtain quality products.…”
Section: Introductionmentioning
confidence: 99%